2016
DOI: 10.1080/09540121.2016.1195486
|View full text |Cite
|
Sign up to set email alerts
|

Obligation to family during times of transition: care, support and the response to HIV and AIDS in rural South Africa

Abstract: In rural South Africa, high HIV prevalence has the potential to affect the care and support that kin are able to provide to those living with HIV. Despite this, families seem to be largely resilient and a key source of care and support to family affected by HIV. In this article, we explore the motivations for the provision of care and support by kin. We use the results of a small-scale in-depth qualitative study conducted in 10 households over 6 months in rural KwaZulu-Natal, South Africa, to show that family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
1
15
0
2
Order By: Relevance
“…In contexts of high fluidity, it is the granular adaptability of health services to client needs that enables care continuity. The paper contributes to a growing body of literature that aims to develop a more nuanced conceptualization of household fluidity in the context of HIV . This manuscript is about understanding the inherent fluidity in the lives of people living in the highest HIV prevalence region of the world and how this fluidity intersects with their engagements with HIV services.…”
Section: Discussionmentioning
confidence: 99%
“…In contexts of high fluidity, it is the granular adaptability of health services to client needs that enables care continuity. The paper contributes to a growing body of literature that aims to develop a more nuanced conceptualization of household fluidity in the context of HIV . This manuscript is about understanding the inherent fluidity in the lives of people living in the highest HIV prevalence region of the world and how this fluidity intersects with their engagements with HIV services.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear how context-specific associations between social connectedness and cognitive health might be. Although norms of caregiving and mutual reciprocity beyond immediate relations are fluid in many LMICs, they often remain stronger than in higher-income settings ( Knight et al, 2016 ; Ugargol and Bailey, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…They say little about how patterns of care responsibilities come about, and how they are bargained and negotiated between different family members. Research on other aspects of care-giving demonstrates the value of more contextualised and nuanced analysis (Knight, Hosegood, & Timaeus, 2016). Social science research has revealed important insights about gendered aspects of care-giving in LMICs, particularly with reference to childcare or care for adults with HIV/AIDS (Razavi, 2011; UN Research Institute for Social Development [UNRISD], 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In countries like Mexico and Peru, accelerated population ageing is leading to a growing prevalence of old age care dependency (Jackson, Strauss, & Howe, 2009;Rossel, 2016). Across Latin America as a whole, as well as most other low and middle income countries (LMICs), formal care services for dependent older people remain limited and so the responsibility for care-giving falls almost exclusively on family carers (Bernabe-Ortiz, Diez-Canseco, Vásquez, & Miranda, 2016;Camarano & Leitão e Mello, 2010; Economic Commission for Latin America and the Caribbean [ECLAC], 2012;Flores-Castillo, 2012).…”
Section: Introductionmentioning
confidence: 99%